(untitled) (Research, Society and Development, 2020)
Hepatitis C is a global health problem and is a major cause of chronic liver disease on all continents. The objective of the article is to present the epidemiological profile of hepatitis C in the State of Piauí. This is a retrospective, cross-sectional and descriptive study with a quantitative and evaluative approach. Records and medical records were collected at SINAN, referring to patients diagnosed with the Hepatitis C Virus who were treated between 2014 and 2016 in the state of Piauí. The results obtained showed a prevalence of males, however, low education is equivalent for both sexes. The municipalities with the highest notifications were: Teresina (capital of the state), followed by Parnaíba, Piripiri and Picos. It was possible to identify the genotypes and their subtypes, type 1 (with subtypes 1a and 1b) being the most reported in the State, followed by genotype type 3. The transmission routes found were: parenteral, blood and sexual transfusion. As for treatment, it is observed that in 2014, the double therapy was performed with the drugs Peginterferonalfa and Ribavirin; in 2015 and 2016, the therapy was updated for Sufosbuvir, Simeprevir and Daclastavir, however, the treatments varied according to the identified genotype. It appears that between 2014 and 2016 there was a discrepancy between the notifications of the cases notified in SINAN and the registration of the number of patients in the medication dispensing, where this was shown to have the highest records. Data that should draw the attention of the State to the decentralization of notifications.